FAU-UEA: proposta para faculdade de arquitetura e urbanismo do Estado do Amazonas - Pinheiro de Lima, Raísa (Brasil, 2022)
The work was prepared due to the need to create a Faculty of Architecture and Urbanism that would meet the demands required by the course and that, unfortunately, are not met by the institutions offering it in the State of Amazonas. The development of this project, shown throughout the magazine, comprised the history of the course of Architecture and Urbanism in Brazil, from its inception to the present day, and was inspired by several professionals graduated since then. To create a new teaching institution, we sought to understand the course since its inception to rescue the base principles of Architecture and then, merge them with the current needs of the area and the target audience, considering yet the climatic characteristic of the Amazon region and the importance of using new sources of sustainable materials. For this, it was essential to research and understand how each material responds to the action of the sun on the implanted terrain, and the necessary artifices to circumvent the problem.